Analisis penerapan pendidikan karakter dalam pembelajaran matematika berbasis daring siswa SMP - Dotari, Apriliza; Komalasari, Resti (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
Character values ​​education is expected to improve the quality in the learning process, besides that it can also affect student learning outcomes so that students not only get cognitive, affective and psychomotor abilities from school but students also get character learning that will shape student character even better. . The purpose of this study was to determine the process and results of character values ​​education at SMP N 10 Bengkulu City in class VIII A. In this study the technique used was a qualitative method with case studies, then the instrument used wasobservation, interviews, open questionnaires and documentation. The results of this study are the teacher will prepare models and methods of learning mathematics which will later be associated with character values ​​such as honesty, discipline, independence, responsibility and hard work. One example is by making story problems on social arithmetic material about honest characters. Furthermore, because it is still a pandemic period so students learn to use the online system, the obstacle that often occurs is that there are still some students who still violate the rules or are not disciplined either from attendance through the Google Classroom application until they are late in collecting assignments. The solution is that the teacher takes a personal approach to each student.